Health equity and system resilience during crises - ensuring healthcare for refugees based on lessons from Iran’s response to the 2021 Afghan migration - Karimian, Zahra; Hashjin, Asgar Aghaei; Bellizzi, Saverio; Winkler, Volker (International journal for equity in health, 2025)
Sudden influxes of displaced populations can strain health systems, especially in low- and middle-income countries. Iran hosts one of the world’s largest migrant and refugee populations -predominantly from Afghanistan - and provides inclusive access to public health and education services. In August 2021, the crisis in Afghanistan triggered a sharp increase in Afghan arrivals to Iran, raising healthcare demand amid the COVID-19 pandemic. This study examines how one of the largest public health networks in Tehran responded to this surge and the resulting impact on equitable service coverage and system resilience.